The effect of microorganisms of raw milk on free amino acid and free D-amino acid contents of milk and dairy products - Albert, Csilla; Pohn, Gabriella; Lóki, Katalin; Salamon, Szidónia; Albert, Beáta; Sára, Péter; Mándoki, Zsolt; Csapóné Kiss, Zsuzsanna; Csapó, János (Acta Agraria Kaposváriensis, 2007)
In the first part of our experiments it was established that certain microbe species causing mastitis (inflammation of the udder) (Streptococcus dysgalactiae, Streptococcus uberis, Escherichia coli, Staphylococcus aureus, Pasteurella multocida, Corynebacterium bovis, Arcanobacter pyogenes and Pseudomonas aeruginosa) contributed to D-aspartic acid, D-glutamic acid and D-alanine contents of milk to a different extent, however, examination of amino acids was only partially suitable for identification of pathogen microbe species causing mastitis. Out of D-amino acids of peptidoglycan D-glutamic acid contents provides the possibility of identifying the microbes. Based on D-aspartic acid contents only Mastitest-negative milk sample and the species Staphylococcus aureus can be identified. On the basis of D-alanine contents microbes examined by us with the exception of the species Escherichia coli, Streptococcus aureus and Pseudomonas aeruginosa can be identified. Free amino acid contents of milk derived from mastitic udder with mastitis caused by the individual bacterial species do not differ significantly from each other, there are, however, such free amino acids whose proportion is characteristic of the given microbe species. The species Streptococcus uberis produces the least glycine, for the Escherichia coli is typical the very high phenylalanine contents. Milk derived from mastitic udder with mastitis caused by Pseudomonas aeruginosa contains the most of free lysine. In the second part of our researches we have examined free amino acid and free D-amino acid contents of milk samples with different germ numbers and composition of dairy products produced from them. Total germ number of milk samples examined varied from 1.23·106 to 2.95·106. It was established that with an increase in germ number concentration of both free D-amino acids and free L-amino acids increased, however, increase in D-amino acid contents was bigger considering its proportion. There was a particularly significant growth in the germ number range of 1.5·106 to 2.9·106. In the course of analysis of curds and cheese samples produced using different technologies we have come to the conclusion that for fresh dairy products and for those matured over a short time there was a close relation between total germ number and free D-amino acid and free L-amino acid contents, ratio of the enantiomers was not affected by the total germ number, however. For dairy products, however, where amino acid production capability of the microbial cultures considerably exceeds production of microorganisms originally present in the milk raw material, free amino acid contents of the milk product (both D- and L-enantiomers) seem to be independent of the composition of milk raw material.